FAKTOR-FAKTOR YANG MEMPENGARUHI KEPATUHAN IBU BALITA UNTUK MENGUNJUNGI MANAJEMEN TERPADU BALITA SAKIT (MTBS) SECARA TERATUR - Ana Ratnasari; Sugi Purwanti (Kesmas Indonesia, 2013)
ABSTRACT Integrated Management of Childhood Illness is one of ways to decrease number of baby and children under five year neonatal. However, number of baby and children under five year neonatal still high, number of baby neonatal 10,3/1000 live births and number of children under five year neonatal 11,46/1000 live births.Knowing factors affecting dicipline of mother’s children under five year to visit Integrated Management of Childhood Illness regularly program.Survey analytic research with cross sectional design. Research instruments used structure questioner. Number of sample was 90 respondents used statistic chi square test.Number of mother’s child obedience in Kemranjen Public Health Center II mostly indiscipline 65,56% (59 people), number of mother’s children under five year education mostly elementary school and junior high school 77,78% (70 people), economic status of mother’s children under five year mostly sufficient 46,67% (42 people), and mother’s children under five year attitude mostly less 55,55% (50 people). There was a significant affect among mother of children under five year between mother of children under five year discipline to visit regularly of Integrated Management of Childhood Illness program (p<0,05).Need further approaches by health personnel to mother of children under five year so they can understand the important of discipline to visit Integrated Management of Childhood Illness regularly. Keyword : Discipline, visit regularly, Integrated Management of Childhood Illness (IMCI) Kesmasindo, Volume 6, Nomor 1 Januari 2013, Hal. 12-25